Dielectric Properties of Cryogenic Gas Mixtures Containing Helium, Neon, and Hydrogen. Issue 1 (November 2015) - Graber, L; Kim, W J; Cheetham, P; Kim, C H; Rodrigo, H; Pamidi, S V
Abstract: Past efforts of cooling high temperature superconducting (HTS) power cables by gaseous cryogens focused exclusively on helium. The limited dielectric strength of helium gas necessitated alternatives that could be used in the temperature range suitable for HTS power applications. This paper presents the benefits of gas mixtures containing helium with small concentrations of hydrogen or neon to mitigate the limited dielectric strength of pure helium gas. The expectation was that such gas mixtures could improve dielectric characteristics while maintaining the thermal, non-flammable and non-corrosive properties of pure helium gas. The AC breakdown voltage of helium gas mixtures containing 4 mol% neon or 4 mol% hydrogen respectively have been measured and compared to those of pure helium and pure neon. All measurements were performed at 77 K at gas pressure levels between 0.5 and 2.0 MPa. While the 4 mol% neon mixture did not result in any improvement over pure helium, the 4 mol% hydrogen mixture resulted in 80% higher breakdown strength. This is expected to enable higher operating voltages for gas cooled HTS power devices.